Analisis laporan keuangan Bank Victoria Syariah menggunakan pendekatan Rasio Profitabilitas (ROE) - Firdaus, Maulana; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2026)
This study aims to look at the financial performance of Bank Victoria Syariah over the last five years (2020-2024) using the Return on Equity (ROE) profitability ratio approach. ROE is a key indicator that shows how well a bank can generate profits based on the total equity it holds. The data used is sourced from Bank Victoria Syariah's annual financial statements. The results of this study show that the ROE value increases consistently from 2020-2024, this suggests that banks may be able to better manage equity to generate profits. These findings show that Bank Victoria Syariah is on a positive path to increase profitability and strengthen its position in the Islamic banking industry in Indonesia.